Corynoxeine Supplementation Ameliorates Colistin-Induced Kidney Oxidative Stress and Inflammation in Mice - Yue Liu; Ruichen Zhang; Tony Velkov; Jianzhong Shen; Shusheng Tang; Chongshan Dai (Antioxidants)
This study investigated the protective effects of corynoxeine, a natural alkaline compound, on colistin-caused nephrotoxicity using a murine model. Forty mice were divided randomly into control, corynoxeine-only (20 mg/kg/day, intraperitoneal injection), colistin-only (20 mg/kg/day, intraperitoneal injection), and colistin (20 mg/kg/day) + corynoxeine (5 and 20 mg/kg/day) groups (8 mice in each group). All treatments were maintained for seven consecutive days. Results showed that colistin treatment at 20 mg/kg/day for seven days significantly increased serum urea nitrogen and creatinine levels and induced the loss and degeneration of renal tubular epithelial cells, which were markedly ameliorated by corynoxeine co-treatment at 5 or 20 mg/kg/day. Corynoxeine supplementation also markedly attenuated colistin-induced increases in malondialdehyde levels and decreases in reduced glutathione levels and superoxide dismutase and catalase activities in the kidneys. Furthermore, corynoxeine supplementation significantly decreased the expression of transforming growth factor β (TGF-β) and nicotinamide adenine dinucleotide phosphate hydrogen oxidase 4 (NOX4) proteins and nuclear factor kappa B (NF-κB), interleukin-1beta (IL-1β), IL-6, and tumor necrosis factor-α mRNAs, while it significantly increased the expression of erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) proteins in the kidneys. In conclusion, these results reveal that corynoxeine can protect against colistin-induced nephrotoxicity in mice by inhibiting oxidative stress and inflammation, which may partly be attributed to its ability on the activation of the Nrf2/HO-1 pathway and the inhibition of the TGF-β/NOX4 and NF-κB pathways.